A cross-sectional study of skin prick test to Aspergillus fumigatus antigen in asthmatic patients seen at a tertiary healthcare center - Jayanthi Savio (Indian Journal of Allergy Asthma and Immunology, 2019)
INTRODUCTION: Asthma is a significant public health problem. The severity of asthma varies from patient to patient and the reasons for this are not fully understood. Atopy is known to play an important part in the pathogenesis of asthma. Sensitization to aeroallergens like house dust mite, animal dander from pets and environmental fungi are evaluated in asthmatics. Severe asthma seems to be associated to environmental fungi with sensitization especially to Aspergillus species. AIMS AND OBJECTIVE: The study aimed at determining the prevalence of Cutaneous Sensitization to Aspergillus species by Skin Prick Test (SPT) in moderate- severe asthmatics. MATERIAL AND METHODS: This study was done on 205 clinically diagnosed asthmatic patients, between September 2012 and August 2013. SPT and spirometry was done in all subjects along with a detailed history. RESULTS: The prevalence rate of Aspergillus sensitized patients is 59.5%. Observations of this study also suggest that the severity of asthma is more in Aspergillus sensitized patients when compared to non-sensitized patients and the duration of asthma was more in Non sensitized. There was no significant association between AEC, total IgE levels and Aspergillus species culture positivity in Aspergillus sensitized patients. Aspergillus terreus was the predominant fungal isolate from both SPT positive and negative patient. There was no significant correlation of fungal culture with SPT. CONCLUSIONS: High levels of Aspergillus sensitization is seen in south Indian subjects and is associated with greater severity and shorter duration of asthma.